2012
DOI: 10.1021/jf3009958
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Inhibitory Effect on Pancreatic Lipase Activity of Subfractions from Ethanol Extracts of Fermented Oats (Avena sativa L.) and Synergistic Effect of Three Phenolic Acids

Abstract: The purpose of the present work is to study the pancreatic lipase inhibitory effects of different subfractions (n-hexane, ethyl acetate (EA), n-butanol, and water) from ethanol extracts of nonfermented and fungi-fermented oats and to delineate the interactions of three primary phenolic acids in the EA subfractions. The EA subfraction showed the highest inhibitory effect on pancreatic lipase activity at 1.5 mg/mL compared to the other subfractions, regardless of whether the oats were fermented. Meanwhile, both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
52
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(62 citation statements)
references
References 25 publications
6
52
0
1
Order By: Relevance
“…Measurement of lipase activity was adapted from previous reports [20]. Lipase of porcine pancreas type 2 was dissolved in ultrapure water at 5 mg/mL.…”
Section: Pancreas Lipase Assaymentioning
confidence: 99%
“…Measurement of lipase activity was adapted from previous reports [20]. Lipase of porcine pancreas type 2 was dissolved in ultrapure water at 5 mg/mL.…”
Section: Pancreas Lipase Assaymentioning
confidence: 99%
“…The interaction analysis of chrysin with apigenin on XO activity was carried out according to a previous report [16] with slight modifications. V a and V b represent the relative remaining enzymatic activity of XO in the presence of chrysin and apigenin, respectively.…”
Section: Interaction Analysis Of Chrysin With Apigenin On Xo Activitymentioning
confidence: 99%
“…Theoretically, the possible favorable outcomes for synergism include: increasing the efficacy of the therapeutic effect, decreasing the dosage but increasing or maintaining the same efficacy to avoid toxicity, and providing efficient synergism against target [15]. Cai et al have investigated the synergistic effect of the three phenolic acids in fermented oats, their results indicated that each binary combination of p-coumaric, ferulic and caffeic acid has a synergistic effect [16]. Earlier studies have also shown that hesperidin and diazepam have the synergy in terms of sedative and sleeping, the use of hesperidin may thus decrease the effective therapeutic doses of diazepam [17].…”
Section: Introductionmentioning
confidence: 99%
“…The inhibition ability of these agricultural products are generally correlated to the phenolic content of their solvent extracts; for example, in our earlier study vigna species of legumes extracts with high polyphenol content showed PL inhibitory activity (Sreerama, Takahashi & Yamaki, 2012). Other studies characterized the lipase inhibitory activity specifically correlated to their content of anthocyanins A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 4 (Yao, Xu, Zhang & Lu, 2013), proanthocyanodins (Gu, Hurst, Stuart, & Lambert, 2011;Nakai et al, 2005), flavan-3-ols (catechins) (Grove, Sae-Tan, Kennett & Lambert, 2012;Nakai et al, 2005), and phenolic acids (Cai et al, 2012). In fact polyphenols represent the major class for the PL inhibitors (reviewed by Lunagariya, Patel, Jagtap & Bhutani, 2014).…”
Section: Introductionmentioning
confidence: 99%